Social democracy in the 21st century - Brandal, Nik; Bratberg, Øivind; Einar Thorsen, Dag (Comparative social research ;, 2021)
Social democrats in the Western world look back on a century where growth and expansion of centre-left values seemed, during certain periods of time, to be a law of nature. Today, the so-called golden era from the 1940s to the 1970s is just a distant memory for the social democratic movement. Volume 35 of Comparative Social Research challenges this narrative of the post-war glory of social democracy. It argues that social democracy has been associated too tightly with the specific context of post-1945 and explores the margin for manoeuvre for the social democratic movement, both now and in the future. Contributors to this book explore essential questions for contemporary social democrats, such as; What does social democracy constitute as a set of ideas in the 21st century experiencing rapid technological, economic and demographic change? - Is the narrative of the decline of social democracy warranted, and is there an opportunity for transformation or even rejuvenation? Social Democracy in the 21st Century is an essential reading for academics and researchers of political science and sociology.